Heat shock protein 70 expression protects against sepsis-associated cardiomyopathy by inhibiting autophagy. (May 2021) - Wang, Xiaofeng; Zhu, Yan; Zhou, Qiuxiang; Yan, Yueyue; Qu, Jinlong; Ye, Hongwei
Objectives: Increasing evidence suggests that heat shock protein 70 (Hsp70) has a protective effect in sepsis-induced cardiomyopathy; however, the protective mechanism remains unclear. Methods: Previous studies have also implicated autophagy in sepsis-induced cardiomyopathy. The aim of the current study was to reveal the protective mechanisms of Hsp70 in sepsis-induced cardiomyopathy using a cecal ligation and puncture (CLP) rat sepsis model. The roles of Hsp70 and autophagy in sepsis-induced cardiomyopathy were investigated by pretreating rats with the Hsp70 inhibitor quercetin or the autophagy inhibitor 3-methyladenine (3-Ma) before CLP. We also investigated the protective mechanisms of Hsp70 and the relationship between Hsp70 and autophagy in vitro by stimulating H9c2 cells with lipopolysaccharide (LPS) to simulate sepsis. Results: The result show that inhibition of Hsp70 promoted sepsis-induced death in rats, while inhibition of autophagy inhibited sepsis-induced death. These results suggested that both Hsp70 and autophagy were involved in sepsis-induced cardiomyopathy. Overexpression of Hsp70 in H9c2 myocardial cells in vitro suppressed LPS-induced apoptosis, while inhibition of autophagy with 3-Ma also decreased LPS-induced H9c2 cell apoptosis, suggesting that the protective effect of Hsp70 in sepsis-induced cardiomyopathy was related to autophagy regulation. Conclusion: Overall, these results suggested that Hsp70 protected against sepsis-induced cardiac impairment by attenuating sepsis-induced autophagy.